EVALUASI KINERJA KEUANGAN PADA KOPWAN (BAITUT TAMWIL MUHAMMADIYAH) “DINAR SETIA” DESA MOJOKAMPUNG BOJONEGORO - Ika Puspita Sari (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study aims to evaluate the performance of the cooperative would scope of financial ratio analysis to determine the financial performance. The scope of the health assessment and UJKS Cooperative KJKS includes assessment of several aspects as follows: capital, asset quality, management, efficiency, liquidity, independence and growth, cooperative identity, And Compliance Sharia. The population used in this thesis is a study of Financial Statements Kopwan BTM Dinar Mojokampung Bojonegoro Faithful Village from 2009 to 2011, consisting of a balance sheet and profit / loss. The data collection method used is the approach of Field Studies (Field Risearch). Pngumpulan engineering data through documentation, and questionnaires. Methods and techniques of data analysis using eight methods are: capital, asset quality aspects, management aspects, aspects of efficiency, liquidity aspects, aspects of independence and growth, and the cooperative aspects of identity keptuhan aspects of sharia. Total score achieved Kopwan BTM "Dinar Faithful" Bojonegoro Mojokampung village in 2010 was 61.55 and in 2011 amounted to 65.8, a score of 10 out of a total capital aspect weights 10, 10 asset quality aspects of the total weight of 20, 12 management aspects , 8 of the total weight of 15, the efficiency aspect of a total weight of 10 9.5, 6.25 and 8.75 the liquidity aspect of the total weight of 15, self-reliance and growth aspects of 3.25 and 2.5 of the total weight of 10, the cooperative aspects of identity 2.75 and 6.25 of the total weight of 10, and compliance aspects of sharia 6 of total weight 10. So the predicate obtained Kopwan cooperative BTM "Faithful Dinar" The village is Mojokampung Bojonegoro Fit.